Paleostress analysis of the Yesilyurt-Elazig Fault Zone and its importance for the tectonic evolution, East Turkey - Kokum, Mehmet; Inceoz, Murat (Pergamon-Elsevier Science Ltd, 2020)
The Yesilyurt-Elazig Fault Zone (YEFZ) located in Eastern Anatolia is a morphologically distinct NE-SW trending left-lateral strike-slip fault, about 150 km long. In this study, inversion of fault slip data collected from the YEFZ and tectonic locations of the stratigraphic units are used in order to reveal the tectonic evolution and chronology of faulting from early Paleocene to today. Based on the inversion of about 250 fault slip data, four successive deformation phases are defined in the study area since early Paleocene. The first deformation phase is characterized by N-S compression during the early Paleocene. The second deformation phase is NW-SE extension related to slab steepening and breakoff in late Paleocene-early Miocene. The third deformation phase is a NNE-SSW compressional one in the middle Miocene-early Pliocene. A strike-slip phase with NNE-SSW compression is the fourth and youngest deformation phase in the study area. Dip-slip striations are overprinted by strike-slip striations; we hence interpret that these faults were reactivated under the later stress field. Our results are consistent with other published regional studies.
Keywords: Paleostress; Tectonic evolution; East Turkey; Reactivation